Beringer, Hattaway, Jones, and Still, Jr. The Elements of Confederate Defeat - Nationalism, War Aims, and Religion - Means, Richard (Teaching History: A Journal of Methods, 1991)
The central theme of this book is that the generally accepted military interpretation of Confederate defeat is inadequate to understand the collapse of the Confederacy. The authors assert that the real cause of the defeat was a lack of nationalist feeling, unclear and changing war aims, and a gradual and demoralizing realization that God was not on the side of the South.